Exploring the changes in ecological well-being performance of resource-based cities in China: Origins of loss and driving factors - Jue Wang; Shuangying Hao; Jiaojiao Zhou; Yin Shi (Environmental and Sustainability Indicators, 2025)
Exploring the origins and drivers of ecological well-being performance loss in China's resource-based cities can provide policy references for promoting high-quality urban development. Using the GB-US-EBM model, this study measures the ecological well-being performance (EWP) of 114 resource-based cities in China from 2011 to 2022, disaggregates the components of EWP, and identifies the origins of performance loss. Additionally, the study integrates the index decomposition analysis (IDA) identity with the logarithmic mean divisia index (LMDI) decomposition approach to investigate the factors driving dynamic changes in EWP. The key findings are as follows: (1) From 2011 to 2022, the average annual EWP across all resource-based cities was 0.347, increasing at an average annual rate of 0.33%. Growing cities exhibited the highest EWP, followed in descending order by declining cities, mature cities, and regenerating cities. (2) In the transformation of system efficiencies, growing, declining, and regenerating cities exhibited higher eco-economic efficiency than economic welfare efficiency. (3) Performance loss is primarily attributable to varying levels of input redundancy and output shortfalls. (4) In terms of external drivers, the shift in EWP from negative to positive was primarily driven by economic development, technological research and development, optimization of industrial structure, and reduction of pollutant emission intensity. Based on these findings, resource-based cities in China should prioritize the development of public welfare infrastructure, enhance public services and social security systems, and accelerate green transformation and economic restructuring.